Relationship between the Knowledge of Benefit of Physical Activity and Physical Activity Level among Individuals with Asthma in Kano State, Nigeria - Abubakar, Ibrahim Ahmad; Abdulazeez Shitu, Aisha; Muhammed, Jibril (Journal of Pharmacy Practice and Community Medicine)
Background: Regular physical activity is an important factor in the promotion of health and quality of life among individuals with asthma. There is a dearth of information on the relationship between knowledge of benefit of physical activity and physical activity level among individuals with asthma in Kano State, Nigeria. Aim: To determine the relationship between the knowledge of benefit of physical activity and physical activity level among individuals with asthma in Kano State, Nigeria. Methodology: Seventy-four (74) participants were recruited from two selected hospitals in Kano State in a cross sectional study. International Physical Activity Questionnaire (IPAQ)-short Form and Knowledge Questionnaire were used to collect information on self-reported physical activity in the last 7 days and level of knowledge of benefit of physical activity respectively. Descriptive statistics was used to describe the data and Spearman Rank Correlation test were used to analyze the data at alpha level of 0.05. Results: A positive relationship existed between overall knowledge of benefit of physical activity and physical activity level among the participants. The majority of the participants were males 43 (58.1%). About 41 (55.4%) were in the age group of 18-35 years, most of them 32 (43.2%) were married. Knowledge assessment showed that 56 (75.7%) of them had low knowledge of benefit of physical activity. Physical activity level assessment revealed that 39 (52.7%) had low physical activity level. Negative relationship was observed between knowledge of benefit of physical activity and all socio-demographic studied (age, gender, marital status, tribe, education and occupation). A positive correlation existed between physical activity level and socio demographic variables (age, gender, marital status and tribe) except that a negative correlation was observed only between physical activity level with education and occupation. Conclusion: Knowledge of benefit of physical activity correlates positively with physical activity level among individuals with asthma in Kano State. Study population had low physical activity and low knowledge of benefit of physical activity.
Keywords: Physical activity; Physical activity level; Asthma; Knowledge of benefit of physical activity; Relationship; IPAQ